Phlebotomines (Diptera, Psychodidae) in the Speleological Province of the Ribeira Valley: 2. Parque Estadual do Alto Ribeira (PETAR), São Paulo State, Brazil - Galati,Eunice A. B. (2010)
The Parque Estadual do Alto Ribeira (PETAR) with about 250 caves, in an Atlantic forest reserve, is an important ecotourist attraction in the Ribeira Valley, an endemic area of American cutaneous leishmaniasis (ACL). With the purpose of investigating Leishmania vector species bothersome to humans the sandfly fauna was identified and some of its ecological aspects in the Santana nucleus, captures were undertaken monthly with automatic light traps in 11 ecotopes, including caves, forests, a camping site and domiciliary environments, and on black and white Shannon traps, from January/2001 to December/2002. A total of 2,449 sandflies representing 21 species were captured. The highest values of abundance obtained in the captures with automatic light traps were for Psathyromyia pascalei and Psychodopygus ayrozai. A total of 107 specimens representing 13 species were captured on black (12 species) and white (6 species) Shannon traps set simultaneously. Psychodopygus geniculatus females predominated on the black (43.75%), and Psathyromyia lanei and Ps. ayrozai equally (32.4%) on the white. Nyssomyia intermedia and Nyssomyia neivai, both implicated in the transmission of ACL in the Brazilian Southeastern region, were also captured. Ny. intermedia predominated in the open camping area. Low frequencies of phlebotomines were observed in the caves, where Evandromyia edwardsi predominated Lutzomyia longipalpis, the main vector of the American visceral leishmaniasis, was aslo present. This is its most southernly reported occurrence in the Atlantic forest.